Babaakhun Salimov's Activity in the Khorezm Jadidism Movement and His Historical Place - Bekimmetov Umidjan Tajimuratovich (Zien Journals, 2023)
In the history of every nation, some historical heroes greatly influenced social and political processes with their activities and played an important role in the history of statehood. Babaakhun Salimov was one of those people, the mature representative of the Jadidist movement in Khorezm in the first quarter of the 20th century.
Keywords: Jadidist movement; Khorezm; historical; social